Document Analysis of School District Policies on Advanced Programs, International Baccalaureate, and Dual Credit Programs in the United States - Bonnie Bowman; Connor Moore; Sevket Cetın (Sakarya University, 2014)
The aim of the study was to investigate the similarities and differences among the school district policies on Advanced Placement, International Baccalaureate, and Dual Credit programs across the United States and how complicated the policies are for parents and students to read and comprehend. The study was designed as a document analysis in which a total of forty-two school districts were randomly selected across the nation, and their policies on these three advanced programs were used as the data source. Flesch-Kincaid readability test was employed to measure the readability of the each district policy based on the pattern of reading ease score guideline. In addition, implications for practice were given based on the findings of the study.